METHODS FOR REDUCING THE DURATION OF OSSEOINTEGRATION IN DENTAL IMPLANTOLOGY (Modern American Journal of Medical and Health Sciences, 2025)
This article reviews practical methods to reduce osseointegration time in dental implantology: implant surface modifications (micro-roughness, hydrophilicity, bioactive coatings), biomaterial choices (titanium, zirconia, PEEK-based solutions), photobiomodulation (low-level laser therapy), and biological adjuncts (PRP/PRF, BMP-2, growth factors). Combined, these approaches may accelerate early bone formation, improve implant stability, and enable earlier functional loading. Key limitations include safety considerations, protocol standardization, and cost-effectiveness.